The Relationship Between Personality Type and Job Satisfaction of Physiotherapists in the City of Bandung - Dwi Hiremawati, Anik; Mulyeni, Sri (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Physiotherapists are among the health professionals whose productivity and performance significantly impact job happiness. This study examines the relationship between personality factors and job satisfaction among Bandung's physiotherapists. Methods: Using the Cochran formula, a correlational quantitative technique was used to select a sample of 68 physiotherapists. A modified work satisfaction survey was used to gather data, and personality characteristics were evaluated using the Big Five Inventory (BFI) adaption questionnaire. Results: Regression analysis showed no significant relationship (r = -0.026, p > 0.05) between personality traits and work satisfaction among physiotherapists in Bandung. These findings imply that work happiness is not only determined by personality type. Instead, workload, connections with coworkers, management support, and work environment can be more critical. Conclusion: The results emphasize the necessity of an all-encompassing plan to raise healthcare workers' job satisfaction. Healthcare organizations can improve patient care and results in healthcare settings by implementing focused interventions to boost the well-being and productivity of physiotherapists by recognizing the numerous components that contribute to work satisfaction.